Comprehensive review of Adansonia digitata (Kalpvriksha): Ethnobotany, phytochemistry, and potential applications - Sonu, A K Srivastava; Singh, Arundhati; Singh, Vinay Kumar (Algerian Journal of Biosciences, 2024)
Adansonia digitata (Baobab) is a multi-purpose tree species belongs to family Malvaceae, commonly known as ‘Kalpvriksha’ in Indian Mythology. The Baobab is widely uses, as medicine, food, and beverages. Plant contains calcium oxalate and resin and also has lots of important phytochemical constituents. The tree provides food, shelter, clothing and medicine as well as material for hunting and fishing. Older baobab trees in the Sudan represent potential sources of water for local people and land travellers. Baobab pulp is rich in vitamin C. The leaves of Adansonia are rich in good quality of proteins mostly essential amino acids, minerals and fat in in seeds. A variety of chemicals from A. digitata noted that they belong to the classes of terpenoids, flavonoids, steroids, vitamins, amino acids, carbohydrates and lipids. Fatty acids present in the seed oil include linoleic and oleic acids in high concentration as well as lesser amounts of palmitic, linolenic, stearic and arachidic acids. Numerous studies on the biological activities of baobab have been conducted with promising results including anti-inflammatory, analgesic, anti-bacterial, anti- oxidant, anti-viral activity, anti-diarrheal, anti- dysenteric activity etc.